Human cytomegalovirus interleukin-10 enhances matrigel invasion of MDA-MB-231 breast cancer cells - Valle Oseguera, Cendy A. (Cancer Cell Int, 2017)
BACKGROUND: While some risk factors for breast cancer are well-known, the influence of other factors, particularly virus infection, remains unclear. Human cytomegalovirus (HCMV) is widespread in the general population, and both molecular and epidemiological evidence has indicated links between HCMV and breast cancer. The HCMV protein cmvIL-10 is a potent suppressor of immune function that has also been shown to promote proliferation and migration of breast cancer cells. In this study, the impact of cmvIL-10 on tumor cell invasion through a simulated basement membrane was investigated. RESULTS: MDA-MB-231 breast cancer cells exhibited invasion through a matrigel layer that was significantly enhanced in the presence of either purified cmvIL-10 or supernatants from HCMV-infected cells containing secreted cmvIL-10. Transcriptional profiling revealed that cmvIL-10 altered expression of several genes implicated in metastasis. Exposure to cmvIL-10 resulted in higher MMP-3 mRNA levels, greater protein expression, and increased enzymatic activity. Treatment with cmvIL-10 also increased expression of both urokinase plasminogen receptor (uPAR) and plasminogen activator inhibitor-1 (PAI-1), which can stimulate MMP-3 activity and have previously been identified as poor prognostic markers in breast cancer patients. Finally, MDA-MB-231 cells treated with cmvIL-10 showed significant downregulation of metastasis suppressor 1 (MTSS1), a scaffolding protein that regulates cytoskeletal rearrangements and is frequently lost in metastatic tumors. CONCLUSIONS: HCMV, and in particular the secreted viral cytokine, cmvIL-10, can induce cellular changes that facilitate cell migration and invasion. These findings indicate that HCMV may be associated with promoting the malignant spread of breast cancer cells and suggest that antiviral treatment may be a useful complement to chemotherapy in some patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12935-017-0399-5) contains supplementary material, which is available to authorized users.